Produção, Caracterização e Comportamento Eletroquímico de Eletrodos de Grafite Recobertos com PbO2 - Dias, Claudiane de Abreu (2011)
We attempted to produce graphite electrodes coated with PbO2 for use as current collectors positive battery lead acid. As one of the techniques use to convering the Polymeric Precursosrs Method, knwon as the Pechini Method. We also performed electrochemical coating. In the chemical method, resins containing Pb were painted on substrates of graphite C calcined or simply calcined in crucibles at different temperatures and characterized by X-ray diffraction. The XRD patterns obtained for oxides characterized by X-ray diffraction led to changes in some synthesis parameters, such as calcination temperature, calcination time, modification of pH and incorporation of additives (ammonium persulfate and hydrogen peroxide). One form of coating was electrochemical cyclic voltammetry, where graphite C electrodes where coated using the solution of lead nitrate 0.1 mol.L?¹ + nitric acid 0.05 mol.L?¹. It was also tested the use of additives : TEAB, sorbitol, SDS and SPT. It was stabilished the relation of the potentiostatic steps in the coating with using additives, TEAB, SDS and the speed of nucleation. The porosity of the graphite electrodes was reduced by impregnation of paraffin in the graphite substrate. The Sharifker and Hills`s theory was applied to investigate whether the nucleation was instantaneous or progressive. The galvanostatic study was conducted using 1, 2, 4 e 6 mA range if the deposition time. We also tested the additives TEAB, SDS e sorbitol. Finally, it was performed cyclic voltammetry of PIGEs with and without coationg in H2SO4 0,5 mol.L?¹, H2SO4 2,0 mol.L?¹ and H2SO4 4,6 mol.L?¹ and evaluated its stability with increase in cycling.